PENGARUH LIKUIDITAS, AKTIVITAS DAN SIZE TERHADAP PERUBAHAN LABA PADA PERUSAHAAN SEKTOR INDUSTRI DASAR & KIMIA YANG TERDAFTAR DI BEI PERIODE 2018 - 2020 - Hidayat, Solikhul; Alma Tsania, Hilda (Jurnal Rekognisi Akuntansi, 2023)
Abstract This research aims to determine the effect of liquidity, activity and size on changes in profits. This research examines the Basic Industry and Chemical sectors. The companies studied are companies listed on the Indonesia Stock Exchange (BEI) in the 2018 - 2020 period. This type of research is quantitative. The data used is secondary data sourced from annual reports obtained from the official IDX website or www.idx.co.id. The population in this study are basic industrial & chemical companies listed on the Indonesia Stock Exchange (BEI). Sample selection was taken using purposive sampling. The total sample is 90 data from basic industrial and chemical companies registered on the IDX in 2018 - 2020. The statistical analysis method used is multiple regression analysis using SPSS software and grouping data from company annual reports using Microsoft Exel software to calculate the ratio. Data analysis methods include descriptive analysis, classical assumption testing, hypothesis testing and determinant coefficients. Based on the research results, it shows that liquidity as measured by the Current Ratio has no effect on changes in profits. Activity as measured by Total Asset Turn Over has a significant positive effect on Profit Changes. Size has a significant positive effect on Profit Changes. Keywords: Liquidity, Activity, Size, Change